Photocatalytic Degradation Enhancement of Dye on Bi12O17Cl2 through Er³? and Yb³? Doping - Osemeikhian Ogbeifun; Shepherd M. Tichapondwa; Evans M. N. Chirwa (Chemical Engineering Transactions)
Photon upconversion effect employing rare earth lanthanides Ytterbium (Yb3+) and Erbium (Er3+) was harnessed in Bi12O17Cl2 to achieve greater light utilisation targeting the large near-infrared (NIR) region of the solar radiation. In this regard, Er3+ and Yb3+ were doped into Bi12O17Cl2, and the best doping level was determined by measuring the decolourisation rate of rhodamine B on the materials. The photocatalytic decolourisation of rhodamine B dye on Yb3+ and Er3+ doped Bi12O17Cl2 materials was assessed under visible light and natural sunlight. The best-performing materials were 0.12%Er- and 0.48%Yb-Bi12O17Cl2, which showed 2.84 and 6.46 folds better than pristine Bi12O17Cl2. As expected, the materials displayed enhanced performance under natural sunlight compared to visible light, the reason being the conversion of a significant portion of NIR (52 % – 55 % of the solar spectrum) into UV and visible light, achieving greater solar light utilisation. The upconversion effect conferred by rare earth intensifies the irradiation strength on the material, which enhances the photocatalytic processes. The degradation mechanism was investigated, revealing the involvement of O2•– and h+ in the decolourization of the dye. The study findings underscore the potential of utilising natural sunlight, rich in NIR, to activate Bi12O17Cl2 and propel the photocatalytic degradation of pollutants.